Inhibition of epidermal growth factor signaling by the cardiac glycoside ouabain in medulloblastoma. (23rd July 2014) - Wolle, Daniel; Lee, Seung Joon; Li, Zhiqin; Litan, Alisa; Barwe, Sonali P.; Langhans, Sigrid A.
Abstract Epidermal growth factor (EGF) signaling regulates cell growth, proliferation, and differentiation. Upon receptor binding, EGF triggers cascades of downstream signaling, including the MAPK and phosphoinositide‐3‐kinase (PI3K)/Akt signaling pathways. Aberrant expression/activation of EGFR is found in multiple human cancers, including medulloblastoma, the most prevalent pediatric brain cancer, and often has been associated with metastasis, poor prognosis, and resistance to chemotherapy. Na, K‐ATPase is an ion pump well known for its role in intracellular ion homeostasis. Recent studies showed that Na, K‐ATPase also functions as a signaling platform and revealed a role in EGFR, MAPK, and PI3K signaling. While both EGFR and Na, K‐ATPase seem to modulate similar signaling pathways, cardiac glycosides that are steroid‐like inhibitors of Na, K‐ATPase, exhibit antiproliferative and proapoptotic properties in cancer cells. Thus, we sought to better understand the relationship between EGF and cardiac glycoside signaling. Here, we show that in medulloblastoma cells, both EGF and ouabain activate Erk1/2 and PI3K/Akt signaling. Nevertheless, in medulloblastoma cells ouabain did not transactivate EGFR as has been reported in various other cell lines. Indeed, ouabain inhibited EGF‐induced Erk1/2 and Akt activation and, moreover, prevented EGF‐induced formation of actin stress fibers and cell motility, probably by activating a stress signaling response. Na, K‐ATPase has been proposed to act as a signaling scaffold and our studies suggest that in medulloblastoma cells Na, K‐ATPase might act as a check point to integrate EGF‐associated signaling pathways. Thus, Na, K‐ATPase might serve as a valid target to develop novel therapeutic approaches in tumors with aberrant activation of the EGFR signaling cascades.